Velocity-based training: how to apply science, technology, and data to maximize performance - Signore, N. (Human Kinetics, 2022)
Velocity-Based Training takes an in-depth look at the science of VBT as well as its programming and application. Strength coaches, personal trainers, and athletes will learn how and when to incorporate VBT into training programs to help maximize strength, speed, and power gains throughout the year. For years strength coaches relied solely on one-repetition maximum percentages to select loads for specific phases of program design. Today, however, more and more coaches have turned to velocity-based training for its pinpoint accuracy in measuring athletes' explosive power through the monitoring of bar and body speeds. As one of the first books of its kind to feature this exciting new method for increasing explosive power, Velocity-Based Training takes an in-depth look into how to best incorporate velocity-based training (VBT) into an athlete's training program. Nunzio Signore is one of the most passionate, intelligent, and infinitely curious coaches in the strength and conditioning profession. As he proves in this book, he is rapidly becoming a pioneer and one of the "go-to guys" for everything related to velocity-based training (VBT). His work has been an Inspiration to u s here at the FlIorida Baseball Ranch, where we train high-Ievel throwing athletes. We have been utilizing VBT for a little over a year, and our results are remarkable. The introduction of VBT to our process has amped up our training's specificity while providing objective, measurable feedback and fresh motivation for our athletes. In Velocity-Based Training, Signore will show you how bring your athletes to greater levels of strength, speed, and power at a faster rate. You will find the following: